ANALISIS PERAN GURU DALAM MENANAMKAN NILAI KARAKTER/ RELIGIUS DI SEKOLAH DASAR - Nabila Nurul Aida; Yunita Febrianti; Jihan Fitria Maharani; Vita Amalia; Ahmad Hariandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teacher professions have several advantages from other professions. The Javanese term says that the teacher is someone who is believed and imitated (exemplified), is a profession that deserves to be appreciated and upheld. Implementation of these things should be a teacher should be a model to make the educational world based on character, moral and not leave the local cultural wisdom. This study aims to see (1) how the role of teachers as a model in the formation of student character, (2) how the challenge faced by teachers as a model in the formation of student character. The method used in this research is qualitative description. The results of this study indicate that teachers have a complex task and responsibilities towards the achievement of educational goals, teachers are not only required to master the science to be taught, have knowledge and teaching skills, teachers are also required to have morals, characters and personality that can be made role model for learners.